Use of Dyed Fiber Yarn for Warp Yarn of Denim Fabrics - Matluba Adashbayevna Doniyorova; Gulbahor Qurol qizi Sadikova (Zien Journals, 2022)
This article is devoted to the problem of preparing threads from dyed fibers for denim. It is also about identifying shortcomings in the production of warp threads at the jeans and weaving enterprises of Uzbekistan. There are several disadvantages to dyeing warp threads. Therefore, research is being done on spinning dyed fibers or dyeing soft yarns.
Keywords: denim; cotton fiber; deep processing; dyeing